Syndrome venae cavae inferior – case report - Mladenović, Bojan; Mladenović, Nikola; Brzački, Vesna (Acta medicae Medianae, 2021)
Vena cava inferior (VCI) colect bload from the abdomen and inferior extremitets, goes up through the retroperitoneum and cams in to the right athrium of heart. Opstruction of VCI can be caused by the tromb or the  tumor who made compresion from the outside. Opstruction of the VCI causes edema of the inferior extremitets, dilatation of the vein at inferior part of the abdomen which used like colaterals. In the diagnostic this disordes it is nessesery to make labaratory, ultrasaund of the abdomen, computerised tomography, and finally cavography. On that way we made the reason of the opstruction, and detect colateral circulation,  and eventualy plan sugical reconstruction.
Keywords: donja šuplja vena; ascites; retroperitonealni tumor